FORMATION OF PROFESSIONAL ABILITIES OF FUTURE PRE-SCHOOL TEACHERS OF EUROPEAN INTEGRATION - Volynets, Yuliia; Volynets, Catherine (Educological discourse, 2020)
The article reveals the problem of the formation of professional abilities of future preschool teachers in the context of European integration. The state of the problem under study in modern theory and practice is analyzed; clarified the features of the formation of professional abilities of future preschool teachers; the professional abilities of students -future preschool teachers in the process of educational activity are characterized. Possible ways of intensifying the movement of the modern professional educational system into the European educational and scientific community and promising areas for further research are identified. Exploring the problem of forming the readiness of future specialists in pre-school education to carry out professional activity in the context of European integration, one of the factors is: the transition from productive ideas to a real change of educational space, the implementation of effective retraining of future pre-school teachers, to technologically and methodically update the educational process, to raise the quality of education, to rely on the intrinsic motivation of future pre-school teachers. We have found out that the specificity of professional activity requires the teacher of higher education institution to have certain knowledge and skills, in particular, knowledge of forms and methods of implementation; possessing a system of advanced competencies in the field of technology of modeling, designing and realization of pedagogical process on the basis of features and values orientations of students; changes in traditional technology of interaction with students. During the preparation of the student-future specialist in pre-school education for the organization of professional activity, it is assumed that the teacher as a subject of the specified activity of a complex of special abilities, among which are analytical, communicative, research, reflexive, presentation abilities. They are in the skill to effectively carry out their professional activities and teach students; to activate their cognitive activity by posing educational problems; organize research activities of different levels of independence according to the individuality of each student.